(untitled) - Stern, H. H. (Oxford, 1992)
The book is divided into four parts. *) Policy and Practice provides discussions of language teaching analysis and the processes of curriculum development, implementation, evaluation, and research. *) Defining Objectives considers the role of objectives in language teaching, and focuses on the four objectives of language proficiency, knowledge, affect, and transfer. *) Content Options deals with four main content areas: target language, target culture, communicative activities, and general language education. *) Teaching strategies presents a discussions of instructional options based on the following dimensions: intralingual-crosslingual, analytic-experiential, and explicit-implicit.
Keywords: Language and languages; Study and teaching